Design of a low-voltage portable CMOS FM receiver - Loa, Kok Kiat. (2008)
Design the fundamental blocks of a portable FM radio receiver using 0.25 mm CMOS transistor model provided by the Singapore Charted Semiconductor Manufacturing (CSM), with a voltage supply at 1.5 V.